2002
DOI: 10.1177/109019802237938
|View full text |Cite
|
Sign up to set email alerts
|

Making the Most of Collaboration: Exploring the Relationship Between Partnership Synergy and Partnership Functioning

Abstract: Considering the challenges inherent to collaboration and the time it takes to achieve measurable outcomes, partnerships need a way to determine, at an early stage, whether they are making the most of collaboration. The authors have developed a new measure, partnership synergy, which assesses the degree to which a partnership's collaborative process successfully combines its participants' perspectives, knowledge, and skills. This article reports the results of a national study designed to examine the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
360
1
10

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(388 citation statements)
references
References 27 publications
13
360
1
10
Order By: Relevance
“…They found that the ability of partnerships to achieve a high level of synergy is related to the sufficiency of the partnership's nonfinancial resources (i.e., knowledge, skills, and expertise; perceptual, observational, and statistical information; connections to people, organizations, and groups; legitimacy and credibility; convening power). 105 Partnerships with many different kinds of participants have a greater variety of nonfinancial resources with which to create synergy than partnerships with a few homogeneous partners.…”
Section: 395152mentioning
confidence: 99%
See 3 more Smart Citations
“…They found that the ability of partnerships to achieve a high level of synergy is related to the sufficiency of the partnership's nonfinancial resources (i.e., knowledge, skills, and expertise; perceptual, observational, and statistical information; connections to people, organizations, and groups; legitimacy and credibility; convening power). 105 Partnerships with many different kinds of participants have a greater variety of nonfinancial resources with which to create synergy than partnerships with a few homogeneous partners.…”
Section: 395152mentioning
confidence: 99%
“…26,95,112 In empirical work, leadership and certain aspects of management have been shown to be correlated closely with the ability of collaborations to create synergy and to solve community-level problems. 105,112 The process characteristics in the model explain how leadership and management affect these outcomes. Moreover, they provide a useful lens for identifying important attributes of leadership and management.…”
Section: Leadership and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In the summer of 2012 and 2015, Geriatric Cooperative members completed the Partnership Self-Assessment Tool (PSAT; http://www.lmgforhealth.org), a standardized tool that identifies effectiveness related to synergy, leadership, efficiency and sufficiency of resources (Lasker et al 2001;Wiess et al 2002). In addition, experience-based design (EBD) (Bate and Robert 2006) methodology was used to gather personal stories from individuals with responsive behaviours, their caregivers and staff that described the emotional touch points associated with healthcare journeys.…”
Section: System Coordination and Managementmentioning
confidence: 99%